Pengaruh Perencanaan Sdm, Iklim Kerja, Punishment Dan Reward Terhadap Semangat Kerja Pegawai Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kabupaten Empat Lawang - Tias, Iilva; Nisma Aprini; Marko Ilpiyanto (Universitas Dehasen Bengkulu, 2025)
The purpose of this study was to determine and analyze the influence of HR planning, work climate, Punishment and Reward individually and together on the work spirit of employees of the Human Resources Development and Personnel Agency of Empat Lawang Regency. The research method used in this study is a quantitative method using a questionnaire distributed to respondents. Data quality testing using validity tests, reliability tests and normality tests. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial tests, simultaneous tests and coefficients of determination. The results of the analysis obtained HR planning, work climate, Punishment and Reward have a significant effect individually and together on the work spirit of employees of the Human Resources Development and Personnel Agency of Empat Lawang Regency.